Salt and Pepper Noise Removal Filter for 8-Bit Images Based on Local and Global Occurrences of Grey Levels as Selection Indicator - Irum, Isma; Sharif, Muhammad; Raza, Mudassar; Yasmin, Mussarat (Nepal Journal of Science and Technology, 2015)
A spatial resolution decision based trimmed moving window filtering method has been proposed for salt andpepper noise removal. It provides a criterion for the selection of neighboring pixels based on the probabilities of local and global occurrences of grey levels of noisy image. It works well for the high noise densities up to 90% and contributes very effectively in estimating the true or near to true values of the original image. In order to measure the quality of image, well known quantification measures SSIM and PSNR are used. The method is compared with other existing techniques and shows that it outperforms other methods in terms of PSNR. DOI: http://dx.doi.org/njst.v15i2.12128 Nepal Journal of Science and Technology Vol. 15, No.2 (2014) 123-132